Improving Student Learning Outcomes Through Model Problem Based Learning on Economics Subjects Class X in SMAN 2 Pasir Limau Kapas Year 2023/2024 - Eva Nizar; Harahap, Fitriani (Journal of General Education Science, 2024)
Research is to increase the interest and learning outcomes of class This research is classroom action research (PTK) which was carried out in 2 cycles and each cycle consisted of 1 meeting. This research was conducted in class X SMAN 2 Cotton Lime Sand . Data collection techniques use test techniques. Test techniques are used to measure student learning outcomes, while participating in learning using the PBL model. The results of this research show an increase in the completeness of learning outcomes, interest in learning from previous conditions using PBL up to cycle II. The increase in learning outcomes obtained has reached the specified success indicators, namely learning outcomes in cycle II increased to 100 % from pre-cycle , namely 34 %, after using the PBL model in cycle 1 increased to 74 % in cycle II student learning outcomes increased to 100 %. This increase shows the success of implementing the PBL learning model, thus it can be concluded that student economic learning outcomes have increased increase through the PBL learning model has been successfully carried out.